A bifunctional peptide–selenium nanocomposite for lysosomal degradation of PD-L1 and enhanced cancer immunotherapy - Wang, Yang; Feng, Jun; Yan, Jin; You, Weiming; Yan, Siqi (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint blockade (ICB) therapies that inhibit PD-1/PD-L1 signaling have revolutionized oncology, yet their benefits are constrained by limited penetration into tumor tissues, inability to eliminate intracellular PD-L1, and the emergence of resistance pathways. Approaches aimed at promoting intracellular PD-L1 degradation and reshaping the tumor immune microenvironment hold promise for overcoming these therapeutic barriers.MethodsA bifunctional therapeutic peptide a capable of binding cytosolic PD-L1 and the molecular chaperone HSC70 was synthesized to facilitate chaperone-mediated autophagy–dependent lysosomal degradation of PD-L1. To improve stability and tumor delivery, peptide a was self-assembled with nano-selenium to form SA. SA was characterized by TEM, DLS, and UV–vis spectroscopy. Binding affinity was validated by ITC. Cellular uptake, PD-L1 degradation, and lysosomal trafficking were assessed via flow cytometry, western blotting, and immunofluorescence. Antitumor efficacy was evaluated in CT26 models and MC38 spheroid assays, with mechanistic analysis performed using immunohistochemistry and flow cytometry. Safety was comprehensively assessed.ResultsSA exhibited uniform spherical morphology (~35 nm) and excellent stability. In vitro studies demonstrated enhanced cellular uptake compared to free peptide and dose-dependent PD-L1 degradation (31.1% reduction at 0.6 μg/mL), which was significantly attenuated by lysosomal inhibition, confirming the chaperone-mediated autophagy (CMA)-dependent mechanism. Immunofluorescence analysis revealed enhanced colocalization of PD-L1 with HSC70 and LAMP2-positive lysosomes following SA treatment. In vivo, SA achieved 88.72% tumor growth inhibition, surpassing anti-PD-L1 antibody treatment (66.97%). SA also demonstrated superior efficacy in MC38 tumor spheroid assays across multiple time points (48h and 72h). Mechanistically, SA downregulated PD-L1, increased CD8+ T cell infiltration 9.4-fold, reduced regulatory T cells by 47.81%, and enhanced cytotoxic CD8+ T cell function with Granzyme B and IFN-γ populations increased 6.8-fold and 2.9-fold, respectively. Comprehensive safety evaluation revealed no treatment-related toxicity, with stable body weight, normal hematological parameters, preserved organ histology, and balanced serum cytokine profiles throughout the study period.ConclusionsSA represents a novel intracellular PD-L1–targeted nanoplatform that promotes lysosome-mediated PD-L1 clearance, remodels the tumor immune milieu, and demonstrates superior antitumor performance compared to PD-L1 antibodies. This dual mechanism addresses key limitations of current ICB therapies and supports further clinical translation.